SA Heart Newsletter Autumn 2015 - Authors, Various (SA Heart Journal, 2017)
Irecently followed an online electronic training course in echocardiography and realised that the more I understand the imaging modality, the more I still have to understand. This journey ended with my attendance at SUNECHO 2015 at Tygerberg Medical Faculty. Despite having attended many courses and lectures, Phillip Herbst and his faculty succeeded in demystifying the remaining questions. Their enthusiastic educational and presentation strategy was made possible only because of their experienced in depth understanding of the topic. The department demonstrated the value of teamwork, allowing members of the team to focus on specifi c expertise and excel. This is a course which all fellows, and even trained cardiologists should attend, consider it as re-training. Further opportunities for training and re-training are available on the ESC website.